Pectin-chitosan complex: Preparation and application in colon-specific capsule - Li, Wu; Hao, Wang; Xiaohua, Zhu; Yinchen, Hou; Wangwang, Liu; Gongming, Yang; Aimin, Jiang (International Journal of Agricultural and Biological Engineering, 2015)
Pectin-chitosan complex was prepared as a candidate material for colon-specific capsule. First, the effects of beating on the properties of complex films were explored. Fourier transform infrared (FT-IR) spectroscopy was used to analyze the reaction mechanics, and an in vitro simulation experiment was performed to determine the degradation performance. Second, the capsule was prepared using pectin-chitosan complex as the main raw material; its targeting effect was evaluated and analyzed. Results indicated that the film became smooth and compact by beating. FT-IR data indicated that cross-linking occurred between the hydroxyl group of pectin and the amino group of chitosan to form a network structure. In vitro experiment showed that the pectin-chitosan complex film could not be degraded in the simulated gastric and intestinal fluids. However, pectin-chitosan complex could be degraded in the simulated colonic fluid, so it could be a potential candidate for colon-specific capsule. Because the complex has no ability for forming hard capsule, the carrageenan and starch were added to increase the flexibility, gelation, transparency and mechanical properties of the film. The preferred composition suitable for preparing the capsule was a mass ratio (2:1:1) of pectin-chitosan/carrageenan/starch mixture. The capsule showed excellent features in terms of shape, water content, and brittleness. The drug release rate reached 93.33% in colonic fluid for 1 h when bovine serum albumin was the model drug. Therefore, pectin-chitosan may be considered as a new material for colon- targeted capsule. Keywords: pectin-chitosan complex, polyelectrolyte, carrageenan, starch, capsule, colon-specific drug delivery system DOI: 10.3965/j.ijabe.20150804.1512 Citation: Wu L, Wang H, Zhu X H, Hou Y C, Liu W W, Yang G M, et al. Pectin-chitosan complex: Preparation and application in colon-specific capsule. Int J Agric & Biol Eng, 2015; 8(4): 151－160.